If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12y+13=9y+28
We move all terms to the left:
12y+13-(9y+28)=0
We get rid of parentheses
12y-9y-28+13=0
We add all the numbers together, and all the variables
3y-15=0
We move all terms containing y to the left, all other terms to the right
3y=15
y=15/3
y=5
| 177=n/8+156 | | 3c/4=5c-136 | | 3y/4=5y-153 | | M=4b=3 | | u+308=-6u-28 | | -28p-76=p+475 | | -7.77=-3f+-5.25 | | a-843=-21a-7 | | 5b/8=4b-162 | | x4-12x3+48x2–64x=0 | | b+110=-3b-22 | | c/5=4c-57 | | 3x/4=3x-27 | | n-711=-25n-9 | | j/5=5j-216 | | 5b+11=56-4b. | | 4b+72=b+18 | | 14x+5=9x+33 | | 3c/4=3c-63 | | -1.1=b/2-2 | | 4x+60=x-57 | | -3(4+r)+3=-(4+2r)-2r | | x/3=5x-112 | | 28=11w-4w | | 3n/5=4n-136 | | 6b+48=b-177 | | d/3-2.3=1.6 | | 16b+9=b-411 | | 3c-20=c/2 | | p/5=4p-57 | | 14x+9=x-368 | | 2g+-9.16=0.84 |